Plan maestro de alcantarillado de la parroquia El Chaupi-cantón Mejía - Castillo Cepeda, Alex Danilo (2011)
With the design of the Sewer Master Plan of the Parish EL Chaupi, it is intended to give a definitive solution to the problems of sanitation and evacuation of rainwater in the sector. The main objective of the study is to improve the quality of life, providing the inhabitants of El Chaupi parish with an efficient sewer system for the evacuation of wastewater in three different networks for topographic reasons